Lateral and radial viscosity structure beneath Fennoscandia inferred from seismic and magnetotelluric observations - Ramirez, Florence D.C.; Selway, Kate; Conrad, Clinton P.; Maupin, Valerie; Smirnov, Maxim (Physics of the Earth and Planetary Interiors, 2024)
Fennoscandia is continuously uplifting in response to past deglaciation, termed glacial isostatic adjustment or GIA, and its mantle viscosity is well constrained from ice sheet and sea level data. Here, we compare those GIA-constrained viscosities for the Fennoscandian upper mantle with geophysically-constrained viscosities. We construct the upper mantle viscosity structure of Fennoscandia by inferring temperature and water content from seismic and magnetotelluric (MT) data. Using a 1-D MT model for Fennoscandian cratons together with a global seismic model, we infer an upper mantle viscosity (below 250 km) of ∼1021±2 Pa·s, which encompasses the GIA-constrained viscosities of 1020 − 1021 Pa·s. The GIA viscosities are better matched if the Fennoscandian upper mantle is a wet harzburgite or a dry pyrolite, where pyrolite is ∼10 times more viscous than harzburgite. Using the average temperatures and water contents for harzburgitic upper mantle, the GIA viscosities require 1–4 mm grain sizes indicating a diffusion creep regime. In northwestern Fennoscandia, where a high-resolution 2-D resistivity model is available, greater inferred mantle water content implies viscosities that are 10–100 times lower than those for the Fennoscandian Craton. Our work suggests that the combination of seismic and MT observations can improve upper mantle viscosity estimates, especially for regions with laterally-varying viscosity structures or where GIA constraints are not available. Although our method represents an important step forward, viscosity uncertainty can be further reduced by incorporating additional constraints on rock composition, grain size and mantle stress, as well as more accurate geophysical data, into the viscosity calculation. Validerad;2024;Nivå 2;2024-04-16 (hanlid); Funder: Australian Research Council (FT1500100541); Full text license: CC BY 4.0